Innovation Capability Building through Integrated Professional Certification: Evidence from Acupressure Sport Massage Pathway within Indonesia's Higher Education Ecosystem - Dani Nugraha; Tite Juliantine; Yudy Hendrayana; Sucipto Sucipto; Arien Arianti Gunawan; Mediany Kriseka Putri (National Research and Innovation Agency, Indonesia, 2026)
In the service sector, there is a need for institutional arrangements to link knowledge, competency standards, professional recognition and industry needs to foster innovation capability building. This study aims to explore the potential of integrated professional certification to facilitate capability building in the sport and wellness higher education ecosystem in Indonesia, as a case study, acupressure sport massage certification. Data were gathered using semi-structured interviews with ten informants from professional certification bodies, competency certification institutions, training providers and higher education, as well as field observations, based on an exploratory qualitative case study. Thematic content analysis identifies four major problems: fragmented certification governance, inconsistent alignment of curriculum and competency standards, uneven certification infrastructure, and competing demands for speedy certification and credible quality assurance. The results indicate that certification should not be seen as a tool for employability alone, but as infrastructure for the institutionalization of academic learning into a standardized, assessed and recognized capability. The study extends the innovation capability building to an emerging service sector in an emerging country context, which adds to the STI policy and innovation management. Policy implications involve improving the cooperation between universities and certification bodies, linking the curricula to the national competency standards, defining the professional classification, and making the certification process accessible but challenging.